Food and Tourism Nexus, challenges and opportunities - Delgado, Amélia (2024)
We aim at examining the interplay between tourism trends and nutrition, based on the perspectives from multiple stakeholders. The question: “Can the tourism sector be leveraged to highlight local cultural identity and biodiversity, by promoting local and seasonal foods as distinctive assets?”, encloses political, economic, and environmental challenges. Key themes include the influence of tourism on local food habits and businesses, the spreading out of ultra-processed foods, and the role of digital platforms and social media in shaping food-tourism dynamics. Suggestions on strategies to encourage sustainable practices are sought after.